The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1474-9726.2008.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired temperature‐sensitive paralysis as a biomarker of declining neuronal function in aging Drosophila

Abstract: SummaryGeneral locomotor activity decreases with normal aging in animals and could be partially explained by decreases in neuronal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…Data for ts-paralysis at 25°C were published previously. 10 Whereas mle napts mutants when aged at 25°C only become susceptible to paralysis at 35°C in extreme age, animals reared at a lower temperature show almost complete paralysis at 35°C as early as 10 d in males and 20 d in females ( Fig. 3A and B).…”
Section: Resultsmentioning
confidence: 97%
“…Data for ts-paralysis at 25°C were published previously. 10 Whereas mle napts mutants when aged at 25°C only become susceptible to paralysis at 35°C in extreme age, animals reared at a lower temperature show almost complete paralysis at 35°C as early as 10 d in males and 20 d in females ( Fig. 3A and B).…”
Section: Resultsmentioning
confidence: 97%
“…Rather, drd expression appears to be required for the development of one or more adult tissues during metamorphosis, and the improper development of such tissues in drd mutants leads, within 1–2 weeks, to the death of the adult. It has also been reported that appearance of several age-dependent markers or phenotypes is accelerated in drd mutant adults, suggesting that drd mutants age more quickly than wild-type flies (Reenan and Rogina, 2008; Rogina et al, 1997). In light of this finding, our data raise the intriguing possibility that the rate of aging in adults could be controlled to some degree by events that occur during metamorphosis.…”
Section: Discussionmentioning
confidence: 95%
“…Drosophila undergo a number of functional declines that correlate with increased age and increased mortality rate, including decreased spontaneous movement, decreased climbing speed, decreased memory, decreased heart function, and decreased reproductive capacity (Grotewiel et al, 2005; Iliadi and Boulianne, 2010; Piazza et al, 2009; Reenan and Rogina, 2008). Correlated molecular changes include decreases in protein turnover system activities (Ubiquitin/proteosome and autophagy/lysosomal), corresponding to the increase in abnormal proteins and the age-related up-regulation of Hsps.…”
Section: Hsps Are Predictive Biomarkers Of Life Spanmentioning
confidence: 99%